Dayside Diffuse Aurora and the Cold-Plasma Structuring: A Brief Review - Han, De-Sheng (Frontiers in Astronomy and Space Sciences, 2021)
Diffuse aurora is generated by the precipitation of hot electrons from the central plasma sheet due to wave-particle interaction. Near magnetic local noon (MLN), the diffuse aurora was often observed in structured forms, such as in stripy or patchy. In the magnetosphere, when the hot electrons meet with a cold plasma structure, the threshold of resonance energy for the electrons in the cold plasma region can be lowered, leading to more electrons being involved in the wave-particle interaction and being scattered into the loss cone. As a result, stronger diffuse aurora can be produced in the correspondent region. Based on this mechanism, the structured dayside diffuse auroras have been suggested to correspond to the cold plasma structures in the dayside outer magnetosphere. This brief review focuses on showing that 1) the stripy diffuse auroras observed near MLN are specifically informative, 2) there are two types of diffuse aurora near MLN, which may correspond to cold plasmas originating from inside and outside the magnetosphere, respectively, and 3) we can study the inside-outside coupling by using the interaction between diffuse and discrete auroras observed near MLN.